The effect of working capital management on firms' profitability in Malaysia - Nadzrah, Abdullah (2014)
This study investigates the relationship between working capital management and firms’ profitability in Malaysia. It examines the components in working capital such as days’ accounts payable, days’ accounts receivables, days’ inventory held and cash conversion cycle in relation to return on asset (ROA). In general, this study contributes to the scarce of literature in this area in Malaysia by providing empirical evidences. Data were obtained from DataStream for two sectors in Malaysia. The sectors chosen are construction & material, and food producer sector. The time period for this study covers from year 2008 to 2012. Finding show working capital management affects firms’ profitability. In construction and material sector, ROA has negative relationship with days’ accounts receivable and days’ inventory held, but positive relationship with days’ accounts payable. In food producer sector, ROA has negative relationship with days’ accounts receivable and payable but negative relationship with days’ inventory held. In both sectors, cash conversion cycles are negatively associated with firm profitability. It indicates that longer duration of cash conversion cycle will decreases firm’s profitability